Air pollution control benefits in reducing inter-provincial trade-associated environmental inequality on PM2.5-related premature deaths in China. (20th May 2022) - Dong, Jiaxin; Li, Siwei; Xing, Jia; Sun, Yisheng; Yang, Jie; Ren, Lu; Zeng, Xiaoyue; Sahu, Shovan Kumar
Abstract: Inter-provincial trade may cause transfer of air pollutants and associated health risks, leading to the issue of environmental inequality. Strengthened air pollution control in China over the past years has resulted in improvements in air quality and public health, while its effect in modulating the trade-associated environmental inequality is still unknown. Here we explore the impact of air pollution control on the trade-associated environmental inequality in China not only in terms of traditional emissions-based index, but also in terms of exposure-based index which is more related to health risks. Although the inter-provincial transfer of pollutant emissions were substantially reduced due to air pollution control, the emissions-based index implied that the imbalance of pollutant emissions and value added among the 31 provinces aggravated from 2012 to 2017 in China. Moreover, the exposure-based index suggested that air pollution control reduced the absolute and relative environmental inequality associated with human health risks due to inter-provincial transfer. The cost related to inter-provincial trade was about 5.46 premature deaths per 100 million RMB value added in 2012, which fell to 3.91 deaths in 2017. The average percentage of economic losses to value added of all transfers was 5% in 2012 and dropped to 3.6% in 2017. This study reflects inter-provincial trade-associated transfer and environmental inequality in a more refined and comprehensive way, with a view to providing a reference for inter-provincial economic cooperation and financial compensation. Graphical abstract: Image 1 Highlights: Exposure-based index is used to quantify environmental inequality on health risk. Air pollution control reduced trade-associated transfers of pollutant emissions. The imbalance of emissions and value added aggravated during 2012–2017 in China. Air pollution control reduced environmental inequality associated with human health.